Acetylcholine spasm provocation test by trans‐radial artery and brachial vein approach. Issue 1 (8th December 2018) - Sueda, Shozo; Fujimoto, Kaori; Sasaki, Yasuhiro; Sakaue, Tomoki; Habara, Hirokazu; Kohno, Hiroaki
Abstract: Background: Temporary pace maker is necessary because of transient block or bradycardia during the intracoronary acetylcholine spasm provocation tests based on the Japanese Circulation Society guidelines. Objectives: We examined the feasibility and safety of the acetylcholine spasm provocation test via the radial artery and brachial vein approach. Methods: We tried to perform the acetylcholine spasm provocation tests in 252 patients via the radial artery and brachial vein approach procedures during 5 years. Acetylcholine was injected in incremental doses of 20/50/80 μg into the right coronary artery (RCA) and 20/50/100/200 μg into the left coronary artery (LCA). Back‐up pacing rate was set at 40 beats/min. Positive spasm was defined as transient ≥90% luminal narrowing and ischemic electrocardiographic change or usual chest pain. Results: The procedure success of radial artery and brachial vein access was 94.4% (238/252) and 93.3% (235/252), respectively. We performed 221 patients (87.7%) with acetylcholine tests by radial artery and brachial vein approach. We changed to the brachial approach due to the failures of radial artery access in 14 patients. We also changed to the femoral vein in 11 patients and internal jugular vein in two patients. Back‐up pace maker rhythm was observed in 92.1% (232/252) of all study patients, while it was significantly higher in the RCA testing than that in the LCA tests (84.9% (191/225) vs. 52.2% (131/251), P < 0.001). No irreversible complication was found. Conclusions: We recommend the radial artery and brachial vein approach for safety and convenience when performing the acetylcholine spasm provocation tests.